2005
DOI: 10.1177/000331970505600513
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Benefits of Matrix Metalloproteinase-9 Inhibition by Doxycycline During Experimental Acute Pulmonary Embolism

Abstract: The authors examined whether acute pulmonary embolism (APE) increases lung matrix metalloproteinase (MMP)-2 and MMP-9 activities and whether inhibition of MMPs with doxycycline attenuates the hemodynamic changes associated with APE. Anesthetized male Wistar rats were monitored for mean arterial blood pressure (MAP) and heart rate (HR). Rats in the control group (n = 5) received only saline IV; rats in the embolism (Emb) group (n = 8) received saline IV followed 10 minutes later by an injection of Sephadex micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…In an acute model of pulmonary embolism in rats, within an hour MMP-9 activity increases by 43%, but interestingly, despite known expression of MMP2 by endothelial cells that are affected by embolization, no significant increase is observed in MMP2 activity. Pretreatment of rats with doxicycline attenuated the physiological impairments seen in pulmonary embolism and blunted the increase in lung MMP9 activity (207). This study exemplifies how pharmacological strategies targeting specific MMPs with selective inhibitors are necessary in treatment of disease.…”
Section: Matrix Metalloproteinases: To Inhibit or Not Inhibit?mentioning
confidence: 58%
“…In an acute model of pulmonary embolism in rats, within an hour MMP-9 activity increases by 43%, but interestingly, despite known expression of MMP2 by endothelial cells that are affected by embolization, no significant increase is observed in MMP2 activity. Pretreatment of rats with doxicycline attenuated the physiological impairments seen in pulmonary embolism and blunted the increase in lung MMP9 activity (207). This study exemplifies how pharmacological strategies targeting specific MMPs with selective inhibitors are necessary in treatment of disease.…”
Section: Matrix Metalloproteinases: To Inhibit or Not Inhibit?mentioning
confidence: 58%
“…Finally it is seen that pharmacological inhibitors of matrix metalloproteinases such as doxycycline, zinc chelators and batimastat have been used as diagnostic and therapeutic tools in cancer, autoimmune and cardiovascular diseases (32,33). Therefore, the following question comes to mind for our study, wonder if the medications used by patients had impact on the matrix metalloproteinases levels?…”
Section: Matrix Metalloproteinases and Tissue Inhibitors In Pulmonarymentioning
confidence: 98%
“…In a rat model, Palei et al (32) observed that inhibition of matrix metalloproteinases with doxycycline, reduces the hemodynamic changes of acute pulmonary embolism. They found an overt increase in matrix metalloproteinase-2 and matrix metalloproteinase-9 activity of the lung in acute pulmonary embolism and then treatment with L-arginine brought relief in pulmonary hypertension and caused reduction of matrix metalloproteinase-2 and matrix metalloproteinase-9 activity.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors In Pulmonarymentioning
confidence: 99%
“…Experimental evidence indicated that the pathophysiology of PE implies the activation of matrix metalloproteinases (MMPs) (Uzuelli et al, 2008;Dias-Junior et al, 2009;Souza-Costa et al, 2005;Souza-Costa et al, 2007;Palei et al, 2005;Fortuna et al, 2007). Indeed, hemodynamic derangements associated with this condition improved with the inhibition of MMPs.…”
Section: The Role Of Matrix Metalloproteinasesmentioning
confidence: 99%
“…This observation offers an explanation for the hemorrhagic transformation during stroke. It is possible that the MMP inhibitors may decrease the risk of intracerebral hemorrhage or other bleeding complication of TL for acute PE (Murata et al, 2008;Sumii & Lo, 2002;Machado et al, 2009) and may have beneficial hemodynamic effects (Fortuna et al, 2007;Palei et al, 2005).…”
Section: Wwwintechopencommentioning
confidence: 99%